2013
DOI: 10.1111/ijd.12100
|View full text |Cite
|
Sign up to set email alerts
|

In vitro activities of antifungal drugs against dermatophytes isolated in Tokat, Turkey

Abstract: Terbinafine was found to be the most effective antifungal drug against all tested dermatophyte isolates. Griseofulvin was the less active antifungal drug against T. mentagrophytes isolates. Performing antifungal susceptibility testing is especially important for screening the development of antifungal resistance.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

14
27
3

Year Published

2015
2015
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 35 publications
(44 citation statements)
references
References 20 publications
14
27
3
Order By: Relevance
“…Up until now, few reports have evaluated in vitro activity of some antifungal agents against dermatophyte species in Iran [35][36][37][38]. Our results show similarity to some previous studies [9,[39][40][41][42][43] and also in contrast to some other reports [38,44].…”
Section: Discussionsupporting
confidence: 89%
See 1 more Smart Citation
“…Up until now, few reports have evaluated in vitro activity of some antifungal agents against dermatophyte species in Iran [35][36][37][38]. Our results show similarity to some previous studies [9,[39][40][41][42][43] and also in contrast to some other reports [38,44].…”
Section: Discussionsupporting
confidence: 89%
“…Although early studies suggested that the antifungal drugs effective against one species are generally effective against others [6], several reports have shown that different species of dermatophytes have variable susceptibilities to various antifungal drugs [7][8][9]. The infecting species along with the location of the infection and the rate of drug accessibility to infected tissue are major factors that need to be considered for an appropriate treatment [10].…”
Section: Introductionmentioning
confidence: 99%
“…Griseofulvin was the first-line antifungal agent for the treatment of dermatophytoses for many years, but today, it is not widely used (4), due to griseofulvin-resistant isolates of dermatophytes and the existence of strains with elevated MICs to griseofulvin (6,(25)(26)(27). With our results, the MICs of griseofulvin for T. rubrum were in agreement with those reported by Adimi et al (7) and Perea et al (18).…”
supporting
confidence: 91%
“…For many years, griseofulvin was the only approved systemic antidermatophytic agent (4). However, nowadays, many potent antifungal agents are available for the treatment of dermatophytosis, such as allylamines and triazoles, which have more potent activity and fewer side effects (5)(6)(7)(8)(9)(10)(11)(12)(13)(14)(15)(16)(17)(18)(19). The expansion of information on in vitro susceptibility testing of dermatophytes to new antifungal agents will help in the selection and development of antifungal drug regimens.…”
mentioning
confidence: 99%
“…4 Lately however, it has fallen out of favour due to rise in Griseofulvin-resistant isolates of dermatophytes and existence of strains with elevated MIC levels to Griseofulvin. [5][6][7][8] Consequently, allylamines and triazoles with higher efficacies, less side effects and a shorter duration of treatment have become the mainstay of management of most superficial mycoses.…”
Section: Introductionmentioning
confidence: 99%